Oxygen support of physical stress in perindopril-treated hypertensive patients - V. I. Makolkin; Sh. Z. Zambakhidze; D. A. Napalkov; T. N. Apanasenko (Кардиоваскулярная терапия и профилактика)
Aim. To study and assess, with spiroergometry method, main parameters of physical stress (PS) oxygen (O2) support in arterial hypertension (AH) patients receiving combined and monotherapy with an ACE inhibitor perindopril. Material and methods. The study included 30 patients (17 females, 13 males; mean age 55.1±8.4 years) with systolic blood pressure (SBP) 140-180 mm Hg, and diastolic blood pressure (DBP) 90-110 mm Hg. Mean AH duration was 5.4±2.2 years. Due to target organ damage, all participants had high cardiovascular event risk. Results. Twelve-week perindopril monotherapy resulted in BP normalization at rest and in PS, significant increase of anaerobic threshold and O 2 pulse, as well as in non-significant improvement of peak O2 consumption, maximal minute lung ventilation, and breath reserve. Combination of perindopril and nebivolol or indapamide resulted in improving of all PS O2 support parameters. Choosing antihypertensive therapy, individually achieved PS level should be taken into account: if maximal O 2 support levels are achieved in >50% of predicted PS, combined therapy with diuretics and beta-blockers is optimal. Conclusion. Perindopril as combined and monotherapy significantly improved PS O2 support parameters in patients with essential arterial hypertension.